PEMELIHARAAN LINGKUNGAN PERSPEKTIF ISLAM: KAJIAN LITERATUR ATAS KONSEP DAN IMPLEMENTASI FIQH LINGKUNGAN - Erliyana; Imam Syafe’i; Baharudin; Ali Murtadho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The increasingly complex global environmental crisis has not only resulted in ecological degradation but also reflects a weakening of the moral and spiritual relationship between humans and nature. From an Islamic perspective, various studies emphasize the importance of integrating theological values, the principles of maqāṣid al-shari‘ah, and fiqh methodology as an ethical foundation for environmental stewardship. This study aims to develop an integrative model of Islamic environmental jurisprudence (fiqh al-bi’ah) that combines theological dimensions, the maqaṣid framework, and contemporary fiqh methodologies, thereby providing both normative and operational foundations for public policy and socio-ecological practices within Muslim communities. This research employs a qualitative approach using library research. Primary data consist of Qur’anic verses, hadiths, classical and modern scholarly works, and fatwa documents particularly Indonesian Council of Ulama (MUI) Fatwa No. 86 of 2023. Secondary data include books, scientific articles, and research reports related to environmental fiqh. Data were collected through documentation and analyzed using content analysis involving data reduction, data presentation, and conclusion drawing. The findings indicate that Islamic theological principles offer a strong moral foundation for environmental preservation through the concepts of tawḥid, amanah, khilafah, and mizan. Meanwhile, maqaṣid al-shari‘ah effectively expands the objectives of Islamic law to include ḥifẓ al-bi’ah (environmental protection), thus granting strong legal legitimacy to ecological preservation. The study also reveals that environmental fiqh still faces methodological fragmentation and lacks integration within operational legal frameworks. It concludes that an integrative eco-fiqh model that combines theology, maqaṣid, and contemporary fiqh methodology is essential for responding comprehensively to ecological crises and for strengthening the implementation of Sharia-based policies in education, fatwa development, and socio-environmental practices.